Analisis Unsur Kepastian dalam Alat Bukti Sumpah pada Perkara di Peradilan Islam - Nazwatika Maulidhiya; Najla Amali; Akhmad Zubair (PT. Sharia Journal and Education Center, 2024)
AbstractIn the practice of resolving cases in court, of course, many methods are used in the process of proving a case, as well as the evidence submitted. As for the evidence itself in a court case, a judge is free to assess the evidence. With the oath tool submitted by the defendant to strengthen its argument, it has several forms such as witness testimony, testimony, confession, and oath. Where the oath itself is a statement from a person that he said on behalf of his god. And the information given by someone who takes an oath is always considered true, this stems from people's belief that words involving the name of God are not words spoken playfully. Through legal analysis, this article tries to describe how the proof of an oath can be used as evidence in a court of law that can fulfil a settlement in the process of cases in court by providing considerations that apply in the principles of procedural law. Keywords: Oath, evidence, court AbstrakDalam praktek penyelesaian perkara dalam peradilan, tentunya digunakan banyak cara dalam proses pembuktian suatu perkara, maupun juga alat bukti yang di ajukan. Adapun pembuktian sendiri dalam suatu perkara pengadilan, seorang hakim bebas untuk menilai pembuktian. Dengan alat sumpah yang diajukan oleh pihak tergugat untuk menguatkan argumentasinya memiliki beberapa macam bentuk seperti keterangan saksi, persangkaan, pengakuan serta sumpah. Dimana sumpah sendiri merupakan keterangan dari seseorang yang ia ucapkan atas nama tuhannya. Dan keterangan yang diberikan oleh seseorang pelaku sumpah selalu dianggap benar, hal ini bermula dikarenakan kepercayaan orang-orang terhadap perkataan yang menyangkut nama tuhan bukanlah perkataan yang diucapkan dengan main-main. Melalui analisis hukum, artikel ini mencoba menguraikan bagaimana pembuktian sebuah sumpah dapat dijadikan sebagai alat bukti dalam sebuah peradilan dapat memenuhi sebuah penyelesaian dalam proses perkara pada pengadilan dengan memberikan pertimbangan yang berlaku dalam prinsip-prinsip hukum acara.Kata Kunci: Sumpah, bukti, peradilan.